Differential Virulence Among Geosmithia morbida Isolates Collected Across the United States Occurrence Range of Thousand Cankers Disease - Karandeep Chahal; Romina Gazis; William Klingeman; Paris Lambdin; Jerome Grant; Mark Windham; Denita Hadziabdic (Frontiers in Forests and Global Change, 2022)
Thousand cankers disease (TCD), first documented in the western United States in the early 2000s, has spread into nine western and seven eastern states in the United States and northern Italy. TCD incidence and severity differ between eastern and western United States outbreak localities. Black walnut (Juglans nigra) trees, introduced into both urban and plantation settings in the western United States, have been severely impacted as evident by the documented high disease incidence and mortality. However, in eastern United States localities, where J. nigra is native, host-pathogen-vector interactions resulted in two different outcomes: trees either die or partly recover followed by infection. Recent genetic studies on the TCD causal agent, Geosmithia morbida, indicate the spatial genetic structure and high levels of genetic diversity among United States populations. Using detached branch inoculation assays, we reported differential virulence among 25 G. morbida isolates collected across the current distribution range of the disease. As a proxy for virulence, the canker area was measured to 7 days after inoculation. Varying degrees of virulence were observed among tested G. morbida isolates, which was partly explained by their genetic provenance (genetic clusters). Isolates that grouped within genetic cluster 2 (n = 7 from the eastern United States and n = 6 from the western United States; mean = 210.34 mm2) induced significantly larger cankers than isolates that grouped within genetic cluster 1 (n = 12; all western United States isolates; mean = 153.76 mm2). Canker sizes varied among isolates within each genetic cluster and were not correlated with a geographic region (eastern vs. western United States) but rather to the isolated state of origin. Mean canker size also differed in response to isolates that originated from different tree host species. G. morbida isolates collected from Juglans major induced statistically smaller cankers when compared to isolates recovered from undetermined Juglans species but not from J. nigra. In sum, the increased mortality reported for western United States walnut tree populations cannot be explained by a higher virulence of local G. morbida. Plausible explanations for the observed disparity include environmental conditions, such as prolonged drought, greater population densities of walnut twig beetle causing a higher number of inoculation events to individual trees, and multiple introductions of G. morbida originating from multiple locations. Future experimental evaluation should be undertaken to quantify the influence of these factors on the local epidemics.